Metode Penelitian Hukum Progresif dalam Mengidentifikasi 'Pasal Karet' pada Undang-Undang Informasi dan Transaksi Elektronik (UU ITE) dan Urgensinya bagi Demokrasi Digital - Sangkala, Robert; Komala, ⁠Ida; Wibowo, Satria Ari; Roif, Roif; Asari, Ali; Candra, Firman Adi (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
The digital era has revolutionized societal interactions, including expression and democratic participation. However, Indonesia's Law No. 11 of 2008 on Electronic Information and Transactions (UU ITE), revised twice (2016 and 2024), still contains ambiguous provisions known as "rubber articles," such as Article 27 paragraph (3) on defamation. These articles often lead to the criminalization of criticism and restrict freedom of expression, conflicting with digital democracy principles. This study applies progressive legal research methods to identify and critique these articles, emphasizing a dynamic and responsive normative approach to socio-technological dynamics. Through juridical and sociological analysis, the research reveals the urgency of reforming UU ITE to strengthen digital democracy in Indonesia. Findings indicate that a progressive approach can serve as a foundation for reconstructing more inclusive regulations, protecting human rights (HAM) in the digital age, and preventing power abuses. Recommendations include establishing a national digital information commission and substantive revisions to problematic articles.